[Glaumbær Sod Houses] - Streng, Evelyn Fiedler (1975)
Photograph of sod houses at Glaumbær. The white, wooden face of a house sits in hills of grass covered sod in a line of similar structures to the right. A white roof face with a square window peeks out of the hill of grass to the left edge of the photograph. The red roofs of a church peeks over the roof to the left.